Vadba ravnotežja s sistemom REWIRE pri bolnikih po možganski kapi - Rudolf, Marko (Rehabilitacija (Ljubljana), 2018)
Background: Rehabilitation of persons after stroke is using virtual reality (VR) in therapeutic practice more than ever. The objective of our study was to determine whether the balance training exercise within virtual environment can be as effective as the conventional balance training for persons after stroke. We used three specific "exergames" from the REWIRE system designed for balance training that were functionally very close to the conventional balance training for patients after stroke. Methods: Between June 2016 and May 2017, 20 patients of the Department for Rehabilitation of Patients After Stroke of the University Rehabilitation Institute in Ljubljana participated in the study. The participants were randomised into two groups: the experimental group training with additional VR "exergames" and the control group receiving additional conventional balance training. The additional balance exercises were limited to 5 days for both groups. Before and after the exercises, a set of clinical tests (the 10m walking test, the Timed up & go test, the Four Square Step Test and modified sensory integration tests) were conducted. Results: The Timed Up & Go test and the Four Square Step Test showed statistically significant improvements in the test group. The control group showed statistically significant improvement in 10m walk test and also the Timed Up & Go test. However, there were no statistically significant differences between the groups after the exercises. Conclusions: Balance training with REWIRE exergames was relatively simple to use and comparable with conventional balance training in terms of effectiveness. We believe that the additional therapeutic procedure may be useful in rehabilitation of persons after a stroke.
Keywords: balance training; možganska kap; navidezna resničnost; rehabilitacija; rehabilitation; Stroke; Telerehabilitation; vadba ravnotežja; virtual reality; vocational rehabilitation